"Set and forget" does not work when it comes to fissure roosts carved into live trees for bats. Issue 1 (21st July 2022) - Griffiths, Stephen R.; Lentini, Pia E.; Semmens, Kristin; Robert, Kylie A.
Abstract : Interest in carving cavities directly into trees to provide habitat for hollow‐dependent wildlife is rapidly growing among researchers, conservation practitioners, community groups, and land managers. Monitoring programs have shown that some of the designs and approaches used to create these structures encourage uptake by fauna. However, evidence for occupancy of "bat specific" fissure cavities is lacking even though they are already being enthusiastically installed and advocated for by the arboriculture industry. To address this, we conducted a field trial to test the efficacy of carved bat fissure cavities (carved fissures), which had entrances designed to replicate the types of natural cracks and crevices that develop in live tree stems which are commonly used by bats. We found that the entrances to all 174 of the carved fissures we installed across 83 live trees were closed by wound wood growth within 6 years of installation, while some were closed by kino (sap produced by Eucalypteae spp.) flow within as little as 3 months. During surveys conducted while entrances to the carved fissures were still open, we did not record any direct or indirect evidence of bats (or any other vertebrates) using them as roosts. These results highlight the urgent need for systematic research, encompassing a broader range of carved designs, tree species, and environmental contexts to assess whether these types of fissure cavities that are carved into live trees can actually provide habitat for bats in the medium‐ to long‐term.